B.S. Johnson’s The Unfortunates: Revisiting the Elegy - Vanessa Guignery (Études Britanniques Contemporaines, 2011)
B.S. Johnson’s ‘novel in a box’, The Unfortunates, is an original and moving elegy to the memory of his best friend who died of cancer at the age of 29, but the unbound format of the book and the unusual use of blanks have been dismissed by some critics as a mere manifestation of playfulness, a collection of tricks or gimmicks. My contention in this paper is that Johnson’s techniques, far from excluding affectivity and ethics, actually offer new ways of expressing emotion and giving a truthful account of feelings of pain, loss and mourning. On the one hand, the narrator is careful never to over-sentimentalise his discourse, hence instances of self-reflexive irony, mockery or derision to keep pathos at bay. On the other hand, this chronicle of a death foretold is a deeply-felt homage that involves narrator and reader in an ethical encounter with the absent Other.